Disease severity in patients infected with Leishmania mexicana relates to IL-1β. - Edith A Fernández-Figueroa; Claudia Rangel-Escareño; Valeria Espinosa-Mateos; Karol Carrillo-Sánchez; Norma Salaiza-Suazo; Georgina Carrada-Figueroa; Santiago March-Mifsut; Ingeborg Becker (Public Library of Science (PLoS), 2012)
Leishmania mexicana can cause both localized (LCL) and diffuse (DCL) cutaneous leishmaniasis, yet little is known about factors regulating disease severity in these patients. We analyzed if the disease was associated with single nucleotide polymorphisms (SNPs) in IL-1β (-511), CXCL8 (-251) and/or the inhibitor IL-1RA (+2018) in 58 Mexican mestizo patients with LCL, 6 with DCL and 123 control cases. Additionally, we analyzed the in vitro production of IL-1β by monocytes, the expression of this cytokine in sera of these patients, as well as the tissue distribution of IL-1β and the number of parasites in lesions of LCL and DCL patients. Our results show a significant difference in the distribution of IL-1β (-511 C/T) genotypes between patients and controls (heterozygous OR), with respect to the reference group CC, which was estimated with a value of 3.23, 95% CI = (1.2, 8.7) and p-value = 0.0167), indicating that IL-1β (-511 C/T) represents a variable influencing the risk to develop the disease in patients infected with Leishmania mexicana. Additionally, an increased in vitro production of IL-1β by monocytes and an increased serum expression of the cytokine correlated with the severity of the disease, since it was significantly higher in DCL patients heavily infected with Leishmania mexicana. The distribution of IL-1β in lesions also varied according to the number of parasites harbored in the tissues: in heavily infected LCL patients and in all DCL patients, the cytokine was scattered diffusely throughout the lesion. In contrast, in LCL patients with lower numbers of parasites in the lesions, IL-1β was confined to the cells. These data suggest that IL-1β possibly is a key player determining the severity of the disease in DCL patients. The analysis of polymorphisms in CXCL8 and IL-1RA showed no differences between patients with different disease severities or between patients and controls.